1998
DOI: 10.1007/bf01345279
|View full text |Cite
|
Sign up to set email alerts
|

Activation of adenosine A2 receptors enhances high K+-evoked taurine release from rat hippocampus: A microdialysis study

Abstract: The present study was designed to examine which type of adenosine receptors was involved in enhancement of high K(+)-evoked taurine release from in vivo rat hippocampus using microdialysis. Perfusion with 0.5 or 5.0 mM adenosine enhanced high K(+)-evoked taurine release. Perfusion with 2 microM R(-)-N6-2-phenylisopropyladenosine (PIA), a selective adenosine A1 receptor agonist, did not modulate taurine release. Perfusion with 1 microM 1,3-dipropyl-8-cyclopentylxanthine (DPCPX), a selective adenosine A1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This effect of caffeine on taurine homeostasis in the hippocampus of diabetic rats may be related to the ability of adenosine receptors (the only known molecular targets of caffeine) to control osmotic swelling (Wurm et al . 2008) and taurine release from both neurons and glia (Hada et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This effect of caffeine on taurine homeostasis in the hippocampus of diabetic rats may be related to the ability of adenosine receptors (the only known molecular targets of caffeine) to control osmotic swelling (Wurm et al . 2008) and taurine release from both neurons and glia (Hada et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These observations prompt the hypothesis that caffeine neuroprotection may also be related to this ability of caffeine to impact on osmotic adaptation of brain tissue. This effect of caffeine on taurine homeostasis in the hippocampus of diabetic rats may be related to the ability of adenosine receptors (the only known molecular targets of caffeine) to control osmotic swelling (Wurm et al 2008) and taurine release from both neurons and glia (Hada et al 1998). Thus, these effects of caffeine on diabetes-induced neurochemical profile are likely to be central effects, although caffeine consumption has been reported to have peripheral effects that may aid in the control of glucose homeostasis (van Dam and Hu 2005); however we observed that long-term caffeine intake failed to prevent hypoinsulinemia and hyperglycemia in STZ-treated rats, suggesting that these effects of caffeine on hippocampal metabolism are related to blockade of central adenosine receptors rather than peripheral actions of caffeine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that adenosine inhibited the pre‐synaptic release of excitatory neurotransmitters such as acetylcholine and glutamate via A 1 receptors (Fastbom and Fredholm 1985; Kurokawa et al . 1996) and enhanced the release of K + ‐evoked taurine release from rat hippocampus via activation of A 2a receptors (Hada et al . 1998).…”
mentioning
confidence: 99%